2022
DOI: 10.1186/s12954-022-00707-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-injecting non-prescribed substances into vascular access devices: a case study of one health system’s ongoing journey from clinical concern to practice and policy response

Abstract: Background Overdose-associated deaths and morbidity related to substance use is a global public health emergency with devastating social and economic costs. Complications of substance use are most pronounced among people who inject drugs (PWID), particularly infections, resulting in increased risk of hospitalization. PWID often require intravenous access for medical treatments such as antibiotics; however, vascular access may be limited due to the impacts of long-term self-venipuncture. While v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…This case highlights the conundrum that healthcare providers face when caring for PWID. Patients are at increased risk of infection, overdose, and death while adding to the duration cost of their healthcare [ 6 , 7 ]. Despite precautions taken, the patient found an opportunity to use her own VAD, which caused a fatal overdose.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This case highlights the conundrum that healthcare providers face when caring for PWID. Patients are at increased risk of infection, overdose, and death while adding to the duration cost of their healthcare [ 6 , 7 ]. Despite precautions taken, the patient found an opportunity to use her own VAD, which caused a fatal overdose.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review on the topic found a lack of publications on the prevalence and statistics regarding the frequency of SIVAD at the time of this case. Recent studies show an increasing acknowledgment of the need for formal management [ 6 , 7 ]. There was a lack of comprehensive protocols defining the management of patients in the hospital and outpatient settings [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations